Breaking-Away from the Comfort Zones: Postmodernism in Selected Philippine Contemporary Novels in English - Basada, Diana Joy L.; Moyano, Mark Anthony G. (International Journal of Language and Literary Studies, 2021)
The paper tries to prove the existence of postmodernism in selected Philippine contemporary novels, namely: Salamanca (2017), Leche (2011), and Naermyth (2010), by identifying the postmodern characteristics embedded in them. It also discusses the association of the identified characteristics of postmodernism with the overall meaning of the novels. After the analysis, this study yields the following major findings: the characteristics of postmodernism are identified in the selected Philippine contemporary novels in English; these include pastiche, intertextuality, the celebration of little narratives, the technique of using nonlinear narratives, parody, irony, the question of identity, the issue of subjectivity, and magic realism. Furthermore, it is proven that the postmodern characteristics help each of the novels to achieve their overall meanings through contributing to the development of their themes.